Evaluation of Standard Concepts Design of Library Interior Physical Environment - Harindya Putri, Debri (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2016)
Currently the function of a room is not only used as a shelter, the function of the room itself to be increased as a refreshing or relaxation area for users to follow the development of creativity and technology in the field of design. The comfortable factor becomes the main factor that indicates a successful process of creating a space. No exception library. The nature of library seemed stiff because of its function as a place to read, now can be developed and made into more dynamic with the special design concepts or color patterns used. Libraries can be created a special concept that suits the characteristics of the users themselves. Most users of the library, especially in college libraries are teenagers. Naturally, teenagers like to gather with their friends and we have to facilitate this activity in our library design concept. In addition we can also determine the needs of users through research by questionnaireÂ method. The answers of users can be mapped and drawn conclusions. To explore the research, the author reviewed some literature about library interior design and observed the library of Ma Chung University as a case study. The combined results of the method can be concluded and the discovery of ideal standards of physical environment. So, the library can be made as a comfortable reading environment so as to increased interest in reading behavior and the frequent visits of students in the library